‘Trumpism’ as a Dominant Movement in the U.S. Republican Party in the 2020s - P. A. Sharikov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Donald Trump’s decisive victory in the 2024 U.S. presidential election offers a fresh perspective on the nature of ‘Trumpism’, which has now firmly established itself not as a temporary or accidental fluctuation in U.S. political life, but as a stable and powerful social phenomenon. This article attempts to identify the origins and key ideological components of this trend, examining it in the context of contemporary political processes within the Republican Party. The first section of the article traces the changes in Trump’s approach to building relationships with the Republican establishment. It highlights that there were favorable domestic political conditions and an updated campaign strategy that allowed Trump to solidify his electoral position at both regional and federal levels in 2024. This marks a sharp contrast with the 2016 campaign, where he was viewed as an ‘outsider’ and a disruptive actor. The second section delves into the ideology of ‘Trumpism’ in the context of the 2024 presidential election. It notes that while Trump distanced himself from the most radical initiatives of the far-right faction of the Republican establishment during the campaign, his rhetoric was distinctly conservative and combative, especially when contrasted with the conciliatory platform of the Democrats. In conclusion, the article argues that ‘Trumpism’ has evolved into a powerful, independent movement within the Republican Party, one that is likely to maintain its influence in the years to come. At the same time, it suggests that Trump’s and the Republican Party’s victory in the U.S. reflects a broader global trend towards strengthening rightwing ideologies. In this regard, the case of the European Union is particularly noteworthy. It raises the question of how Trump’s victory will impact the positions of conservative and right-populist parties and movements across Europe.